The Role of Vocational Education in Indonesian Gastrodiplomacy: Definition, Literature Review, and Bibliometric Analysis - Maosul, Asep; Barliana, M Syaom; Ana, A; Subekti, Sri (Journal of Vocational Education Studies, 2025)
This study aimed to determine research trends in gastrodiplomacy culinary in Indonesia through a literary review and bibliometric analysis. VOSviewer mapping was used to analyze bibliometric data on Indonesian gastrodiplomacy culinary research. A reference manager application was utilized to collect research data.The study covers literature from 2012 to 2022, revealing that the highest number of gastrodiplomacy studies was conducted in 2021. The analysis also indicates a direct relationship between gastronomy tourism and gastrodiplomacy culinary, primarily linked through thematic terms and country-specific contexts. Furthermore, this study highlights the role of vocational education in Indonesian gastrodiplomacy. Vocational education plays a crucial role in equipping culinary professionals with the skills and cultural knowledge necessary to represent Indonesia’s rich gastronomic heritage on the global stage. By integrating gastrodiplomacy concepts into vocational training programs, culinary students can gain expertise in traditional food preparation, presentation, and cross-cultural communication. The findings of this study are expected to serve as a reference for future researchers exploring the intersection of vocational education, gastronomy tourism, and gastrodiplomacy. Vocational education can actively aid in the global promotion of Indonesian cuisine by providing learners with hands-on skills and cultural insights essential for showcasing this food internationally. This bolsters Indonesia’s efforts in gastrodiplomacy and amplifies its culinary identity on the global platform.